Use of a non-medicated plaster in shoulder tendinopathies - Ricci, Matteo; Micheloni, Gian Mario; Perusi, Francesco; Corbo, Valentina Rita; Vecchini, Eugenio; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2016)
We assessed 20 shoulders with rotator cuff tendinopathy and partial tendon tears treated with FIT® plasters (far infrared technology). The criteria for inclusion were pain at night and during active shoulder movement. Patients with restricted passive movement (adhesive capsulitis) and complete tendon tears were excluded. Two different types of FIT® plasters were used according to the different power of action. Plasters were replaced after 7 days and dismissed after 15 days. The patients were assessed using the VAS pain scale and the Constant Murley score for function. The use of FIT® plasters have shown a certain effectiveness in activation of the endogenous analgesic action, with a role in alleviate painful symptoms and improve function in rotator cuff tendinopathies, without adverse events. On the base of the safety of this technology and promising results of our study, further studies should be encouraged to confirm its effectiveness, increasing the sample number and follow up so as to demonstrate definitely that the use of technologies, on which FIT® plasters is based, may be a valid alternative as “non-medicated pain relief”.